2015
DOI: 10.1039/c5ra09595f
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide(iii) morpholine 4-dithiocarbamate complexes: Pr(iii) derivative shows first example of polymeric lanthanide(iii) dithiocarbamate

Abstract: Three lanthanide(III) morpholine 4-dithiocarbamate complexes [Ln(Phen)(Mph-Dtc)3]· x CH2Cl2 [Ln = Pr (1), Nd (2) and Eu (3); Mph-Dtc = morpholine 4-dithiocarbamate; x = 2 (1) or 1 (2-3)] have been prepared from the reaction of potassium salt of morpholine 4-dithiocarbamate with lanthanide nitrates and phenanthroline. Complexes 1-3 were characterized by varoius analytical techniques and their solid state structures were established by single crystal X-ray diffraction analysis. The Ln(III) ions are nine or eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Room temperature photoluminescence of Eu III diethyldithiocarbamato and diphenyldithiocarbamato complexes was reported by Faustino et al [1]. Mahato et al have reported a series of Ln III morpholine 4-dithiocarbamate complexes with their interesting extended structure in the crystals and the spectroscopic properties in solution [2]. Despite of these studies, the chiroptical properties of lanthanoid(III) dithiocarbamato complexes by means 3-heptafluorobutylrylcamphorate) [11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Room temperature photoluminescence of Eu III diethyldithiocarbamato and diphenyldithiocarbamato complexes was reported by Faustino et al [1]. Mahato et al have reported a series of Ln III morpholine 4-dithiocarbamate complexes with their interesting extended structure in the crystals and the spectroscopic properties in solution [2]. Despite of these studies, the chiroptical properties of lanthanoid(III) dithiocarbamato complexes by means 3-heptafluorobutylrylcamphorate) [11].…”
Section: Introductionmentioning
confidence: 98%
“…Lanthanoid(III) complexes are currently being investigated extensively for a variety of their functionalities and applications, such as optical probes, medicine, microelectronics, and others [1,2]. Among the complexes widely studied, those of sulfur-donating ligands are still limited to report, owing to the unfavorable bond formation between the 'hard acid' lanthanoid ions and 'soft base' sulfur-donor ligands [3].…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide-based complexes are currently being investigated extensively for a variety of functionalities and applications, such as optical probes, medicine, microelectronics, and others. [1][2][3][4][5][6][7][8][9][10][11] However, only limited kinds of metal complexes can be used as the anticancer drug in clinic among which platinum (II) and ruthenium (III) complexes are the most popular studied. Cancer patients undergoing chemotherapy usually possess a chance of 20% suffering Candida infection, and most antitumor drugs show no antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…The complexes exhibited similar absorption spectral pattern in the UV region as shown in Fig.S11. The band at 340 nm was assigned to the intra-ligand charge transfer transition[24,25]. In the visible region, sharp but weak absorption bands and MCD signals characteristic of f-f transitions were observed in the complexes.…”
mentioning
confidence: 98%